A novel elliptic trajectory formula for active RSSI-based antenna tracking algorithm - Iscan, Mehmet; Tas, Ali Ihsan; Gurkan, Berkay; Yilmaz, Cuneyt (SAGE PUBLICATIONS LTD, 2023)
In this study, a novel received signal strength indicator (RSSI)-based tracking algorithm for antenna tracker systems utilizing directional antennas is proposed. This system has two sequential phases, which are the ``Full Area Scan Phase'' and the ``Active RSSI-Based Tracking Phase'' with a unique elliptic trajectory formula for generating an original two-dimensional (2D) RSSI map to detect the maximum signal. An elliptic trajectory paves the way for splitting RSSI measurements into specific regions equally on this map in which any disturbance and noises are eliminated. The proposed method do not require any telemetry data or multiple receivers for antennas. The simulation results showed that the algorithm attained to 98% accuracy with respect to the Global Positioning System (GPS)-based ones. In real-world experiments, it captures the first handshake signal within 6 seconds even when the unmanned aerial vehicle (UAV) positions are uncertain. Furthermore, it is demonstrated that this novel technique can provide a continuous tracking at high resolution with the error value of 0:135 degrees and 0:148 degrees in the elevation and azimuth axes, respectively, compared with the GPS-based one. In conclusion, the simulation and test studies indicated that the proposed method could achieve a higher precision tracking with its advantages against the former methods.
Keywords: Antenna tracker; UAV tracking; directional antenna; received signal strength indicator; RSSI; UAV; LONG-RANGE; AERIAL COMMUNICATION; DESIGN; Automation & Control Systems; Instruments & Instrumentation